IMPLEMENTASI SISTEM INFORMASI AKUNTANSI BAGI USAHA KECIL DAN MENENGAH DALAM MENINGKATKAN AKUNTABILITAS LAPORAN KEUANGAN - Danis Imam Bachtiar; Agus Dwi Atmoko; Tri Sekar Priyanti (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
SME development required Accounting Information Systems ( AIS ) are reliable. Because with the SIA, employers can control and can make the company went public and its resistance to the crisis. Because the help of accounting information systems, many SMEs that will withstand the blows of the financial crisis storm, because every dollar in and out of the company can be well controlled, especially when it's dealing with banks. However, unfortunately too many SMEs are reluctant to apply the accounting information system for various reasons. IT capacity building is one of the important factors that need to be considered for small and medium businesses, and it also can develop the business wheel. IT developments are moving very fast, both in terms of hardware ( hardware ) or software (software ) that can help the performance of the company. With globalization need of the application of technology in every business. Implementation of accounting information systems for small and medium businesses generate report Merchandise Inventory , Purchasing , Sales , Purchase Returns , Sales Returns and Financial Statements . So that the presentation of the report can be presented in easily , quickly and accurately by SMEs . This study was conducted to SMEs especially in the area of business Sokka tile Kebumen in January - October 2013